The impact of parental migration on left-behind children’s tooth health in China - Yunyun Zhang; Kang Du (BMC Public Health)
Abstract Background Parental migration plays a significant role in shaping the health outcomes of left-behind children. However, limited research has been conducted on how parental migration impacts the dental health of these children in China. To address this gap, this study aims to investigate the effects of parental migration on the dental health of left-behind children and explore the underlying mechanisms that contribute to these outcomes. Methods This study utilized data from the first wave of the China Education Panel Survey (CEPS), which included a representative sample of 9,175 junior high school students. Dental caries, the most common dental issue among school-aged children, were employed as the primary indicator of oral health, focusing on both the presence of caries and their treatment. The analysis incorporated multiple methodologies, including the Ordinary Least Squares (OLS) model, instrumental variables approach, and the Propensity Score Matching (PSM) method, to assess the impact of parental migration on the dental health of left-behind children. Results The findings indicated that parental migration did not increase the likelihood of left-behind children developing dental caries. However, it significantly reduced the probability of these children receiving treatment for dental caries. These results were consistent across various robustness tests. Mechanism analysis revealed no significant differences in the consumption of carbonated or sugary drinks between left-behind and non-left-behind children. However, left-behind children were less likely to identify their parents as their primary source of support and experienced lower levels of proactive communication from parents about their challenges compared to their peers. Conclusions The study highlights that although parental migration does not increase the prevalence of dental caries among left-behind children, it contributes to inequities in their access to treatment. Given the serious implications of untreated dental caries, targeted efforts are needed to improve treatment rates among left-behind children.